Word Association of The Covid-19 Terms: Case Study on Indonesian Generation Z - Arti Prihatini (PAROLE: Journal of Linguistics and Education, 2022)
Nowadays, society needs to understand the Covid-19 virus and improve appropriate attitudes and actions, especially Generation Z. The present study aimed to investigate adolescents' knowledge, responses, and attitudes. This research method was a descriptive case study. Data were collected using a free word association test and semi-structured interviews. Respondents amounted to 400 people with an age range of 17-24 years. Simple descriptive statistics with Ms. Excel analyzed the data; then, the data was coded with the Atlas.ti 9 application. The results showed that most Generation Z produced common words than idiosyncratic ones. Based on the lexico-syntactic pattern, nouns were responded by paradigmatic relation, while adjectives and verbs responded by syntagmatic. Based on the collocation, responded words were dominated by lexical collocations, while grammatical collocation responses were minimal. The association of the Covid-19 term represented knowledge of Generation-Z about the definition, symptoms, origin, impacts, efforts to deal with the virus, and the current condition of Covid-19. Generation Z tried to accept the pandemic by interpreting wisdom and hoping that conditions would be better soon. However, few generation-Z responded negatively, suspected a conspiracy, and thought the Covid-19 virus did not exist.